Composite carbon nanotube, antistatic PE tube containing the composite carbon nanotube and preparation process

By using modified carbon nanotubes and composite white carbon black and polypropylene in polyethylene tubes, the problem of electrostatic accumulation of polyethylene tubes is solved, and good antistatic properties and mechanical strength improvement are achieved.

CN119751976APending Publication Date: 2025-04-04JIANGSU NOBEL PLASTICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510057695.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing polyethylene tubes are prone to generate static charges under contact friction, high-speed flow through the drying medium or electric field induction, resulting in sparks, and potentially dangerous.

Method used

Compound carbon nanotubes, including modified carbon nanotubes, composite white carbon black and polypropylene, are used to prepare antistatic PE tubes through the synergistic effect of the dispersion performance of the modified carbon nanotubes and the antistatic properties of white carbon black.

Benefits of technology

Effectively prevent static electricity accumulation, improve the anti-static performance of the pipe, while enhancing mechanical strength and improving the overall performance of the pipe.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a composite carbon nanotube, an antistatic PE tube containing the composite carbon nanotube and a preparation process, wherein the composite carbon nanotube comprises modified carbon nanotubes, composite white carbon black and polypropylene; the antistatic PE tube comprises the following components by weight: 220-260 parts of polyethylene, 45-55 parts of composite carbon nanotubes, 30-40 parts of ethylene propylene diene monomer rubber and 3-5 parts of dispersant. The present application has the effect of improving the antistatic performance of PE pipes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of modified carbon nanotubes, and in particular to a composite carbon nanotube, an antistatic PE tube containing the composite carbon nanotube, and a preparation process. Background Art

[0002] Polyethylene pipe (PE pipe) is a pipe made of polyethylene as the main material. It has a wide range of applications and has excellent resistance to most domestic and industrial chemicals.

[0003] Polyethylene pipe is a thermoplastic resin obtained by polymerization of ethylene. In industry, it also includes copolymers of ethylene and a small amount of α-olefins. Polyethylene is odorless, non-toxic, feels like wax, has excellent low-temperature resistance, good chemical stability, can withstand the corrosion of most acids and alkalis, is insoluble in general solvents at room temperature, and has low water absorption.

[0004] Existing polyethylene pipes have high surface resistance. When the pipe wall is subjected to contact friction or high-speed flow through dry and insulating media, as well as under the induction of electric fields, static charges are easily generated. Static electricity discharge can easily generate sparks, which is potentially dangerous. Summary of the invention

[0005] In order to improve the antistatic performance of polyethylene tubes, the present application provides a composite carbon nanotube, an antistatic PE tube comprising the composite carbon nanotube, and a preparation process.

[0006] In the first aspect, the present application provides a composite carbon nanotube, which adopts the following technical solution: The composite carbon nanotubes include modified carbon nanotubes, composite white carbon black and polypropylene.

[0007] By adopting the above technical scheme, carbon nanotubes can effectively prevent static electricity accumulation and have good antistatic properties. At the same time, white carbon black also has antistatic properties, which can synergistically improve the antistatic properties. At the same time, after combining carbon nanotubes, white carbon black and polypropylene, the overall mechanical strength of the system can be synergistically improved, so that when the prepared composite carbon nanotubes are used in pipes, the overall strength is improved and enhanced; a carbon skeleton material is formed between white carbon black and carbon nanotubes, so that the pipes have good mechanical properties.

[0008] Preferably, the modified carbon nanotubes include carbon nanotubes, polyvinyl pyrrolidone and alkanolamine.

[0009] Although the addition of carbon nanotubes can improve the overall mechanical properties of the system, the high aspect ratio and strong interaction of carbon nanotubes will cause the carbon nanotubes to agglomerate in the system, thereby affecting the overall stability of the system. By adopting the above technical solution, the carbon nanotubes are modified by polyvinyl pyrrolidone and alkanolamine. Polyvinyl pyrrolidone provides greater steric hindrance, and alkanolamine forms electrostatic repulsion, which promotes the dispersion performance of carbon nanotubes. The modification of the two components enables the carbon nanotubes to obtain an unexpectedly uniform dispersion effect in the system, thereby improving the stability of the carbon nanotubes in the tube system.

[0010] Preferably, the modified carbon nanotubes are prepared by the following method: Water, polyvinyl pyrrolidone and alkanolamine are mixed and stirred to obtain a mixed solution, carbon nanotubes and zirconium oxide glass beads are added to the mixed solution, and the mixture is shaken in an oscillating disperser to obtain a carbon nanotube dispersion, and the carbon nanotube dispersion prepared above is dried to obtain modified carbon nanotubes.

[0011] By adopting the above technical scheme, after the carbon nanotubes are modified by polyvinyl pyrrolidone and alkanolamine, the N atoms and ketone groups in the pyrrole ring structure of polyvinyl pyrrolidone and the surface active groups of the carbon nanotubes form a force, and the polyvinyl pyrrolidone is attached to the surface of the carbon nanotubes, which can greatly improve the agglomeration of the carbon nanotubes. There is also an electrostatic repulsion between the alkanolamine and the carbon nanotubes, thereby further improving the dispersion performance of the carbon nanotubes in the system. The combination of the three effectively reduces the agglomeration phenomenon of the carbon nanotubes in the system, and the stability of the carbon nanotubes is improved, so that the comprehensive performance of the prepared composite carbon nanotubes is improved.

[0012] Preferably, the mass ratio of the carbon nanotubes, polyvinyl pyrrolidone and alkanolamine is 1:(0.06-0.08):0.025.

[0013] By adopting the above technical solution, preferably the mass ratio of carbon nanotubes, polyvinyl pyrrolidone and alkanolamine is within the above range, which can further improve the comprehensive performance of the prepared modified carbon nanotubes.

[0014] Preferably, the composite white carbon black is prepared by the following method: The terminal hydroxy dimethyl siloxane is heated, then mixed with boric acid and white carbon black, stirred and then kept warm for reaction, and then cooled after the reaction to obtain composite white carbon black.

[0015] By adopting the above technical solution, terminal hydroxy dimethyl siloxane and boric acid form polyborosiloxane, and then modifying white carbon black, the mechanical properties of the system can be effectively improved. The boron atoms in the Si-OB structure in the polysiloxane molecular chain can form BO electron bridge pairs with oxygen atoms in adjacent chains. This electron bridge pair is a dynamically variable physical crosslink that can absorb a large amount of external energy, thereby improving the damping performance and improving the viscosity of the prepared composite white carbon black, so that the white carbon black can combine the various components in the system, further improving the overall connection tightness of the pipe, thereby improving the overall mechanical strength of the pipe.

[0016] Preferably, the mass ratio of the terminal hydroxyl polydimethylsiloxane to boric acid is 1:(0.16-0.18).

[0017] By adopting the above technical solution, preferably the mass ratio between the terminal hydroxyl polydimethylsiloxane and the boric acid is within the above range, the comprehensive performance of the prepared composite white carbon black can be further improved.

[0018] Preferably, the composite carbon nanotubes are prepared by the following method: Hexadecyltrimethylammonium bromide, water and modified carbon nanotubes are mixed and dispersed to obtain a carbon nanotube dispersion; composite white carbon black and water are mixed and dispersed to obtain a white carbon black dispersion; the white carbon black dispersion is added to the carbon nanotube dispersion, filtered using a microporous filter membrane, and dried to obtain a carbon nanotube-white carbon black composite; polypropylene and the carbon nanotube-white carbon black composite are added to an open mill and blended to obtain composite carbon nanotubes.

[0019] By adopting the above technical scheme, firstly, the functional groups on the surface of modified carbon nanotubes are used to adsorb the cationic active agent hexadecyltrimethylammonium bromide, and then white carbon black is assembled on the surface. The stability of the assembled carbon nanotube-white carbon black in the system is improved, and then it is compounded with polypropylene to further improve the overall mechanical strength such as impact resistance of the system, thereby further improving the comprehensive performance of the prepared pipe.

[0020] Preferably, the mass ratio of the modified carbon nanotubes, composite white carbon black and polypropylene is 1:(2.2-2.7):10.

[0021] By adopting the above technical solution, the mass ratio of the modified carbon nanotubes, the composite white carbon black and the polypropylene is preferably within the above range, which can further improve the comprehensive performance of the composite carbon nanotubes.

[0022] In a second aspect, the present application provides an antistatic PE tube, comprising the following components in parts by weight: 220-260 parts of polyethylene, 45-55 parts of composite carbon nanotubes, 30-40 parts of EPDM rubber, and 3-5 parts of dispersant.

[0023] By adopting the above technical scheme, carbon nanotubes can effectively prevent static electricity accumulation and have good antistatic properties. At the same time, white carbon black also has antistatic properties. When added to the pipe, it can synergistically improve the antistatic properties of the pipe as a whole. At the same time, after combining carbon nanotubes, white carbon black and polypropylene, the overall mechanical strength of the system can be synergistically improved, so that the overall strength of the pipe is improved and enhanced; a carbon skeleton material is formed between white carbon black and carbon nanotubes, so that the pipe has good mechanical properties. At the same time, after white carbon black is blended with EPDM rubber, the mechanical properties of the EPDM rubber material can be improved, further improving the overall mechanical strength of the pipe.

[0024] In a third aspect, the present application provides a method for preparing an antistatic PE tube, which adopts the following technical solution: A method for preparing an antistatic PE pipe comprises the following steps: The polyethylene, the composite carbon nanotubes, the EPDM rubber and the dispersant are mixed and added into an internal mixer for internal mixing. The components after internal mixing are transferred into a twin-screw extruder for extrusion molding to obtain an antistatic PE pipe.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The composite carbon nanotubes are prepared by modifying carbon nanotubes, composite white carbon black and polypropylene. The carbon nanotubes can prevent electrostatic deposition and have good antistatic properties. At the same time, white carbon black also has antistatic properties. After the three are combined, the overall antistatic properties of the system can be effectively improved. At the same time, the composite carbon nanotubes prepared by combining the three have good mechanical strength, which improves the mechanical strength of the tube; 2. The carbon nanotubes are modified by polyvinyl pyrrolidone and alkanolamine. Polyvinyl pyrrolidone can provide greater steric hindrance, and alkanolamine forms electrostatic repulsion, which promotes the dispersion of carbon nanotubes, so that the modified carbon nanotubes can be evenly dispersed in the system, thereby improving the overall stability of the tube system; 3. The terminal hydroxy dimethyl siloxane and boric acid form polyborosiloxane, and then the silica is modified, which can effectively improve the overall mechanical properties of silica. The boron atom in the Si-O-B structure in the polysiloxane molecular chain can form a BO electron bridge pair with the oxygen atom in the adjacent chain, so that the damping performance of the prepared composite silica is improved, and the viscosity of the composite silica is improved, thereby improving the connection performance between the various components in the system, and further improving the stability of the prepared pipe. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments: Description of raw materials: All raw materials in the examples are commercially available, wherein the alkanolamine is triethanolamine (CAS No.: 102-71-6), the terminal hydroxy dimethoxy silane is caprolactone-terminated polydimethylsiloxane (CAS No.: 156327-07-0), and the carbon nanotubes (CAS No.: 308068-56-6) are purchased from Shanghai Liantian Materials Technology Co., Ltd.

[0027] Example 1 Preparation of modified carbon nanotubes: 300 g of deionized water, 0.55 g of polyvinyl pyrrolidone (CAS No.: 9003-39-8) and 0.23 g of alkanolamine were mixed, and the mixture was stirred at a speed of 300 r / min for 15 min to obtain a mixed solution. 9.22 g of carbon nanotubes (CAS No.: 308068-56-6) and 150 g of zirconium oxide glass beads were added to the mixed solution, and the mixture was oscillated in an oscillating disperser at an ambient temperature of 25° C. for 6 h to obtain a carbon nanotube dispersion. The carbon nanotube dispersion prepared above was dried in a vacuum drying oven at 80° C. for 12 h to obtain modified carbon nanotubes.

[0028] Preparation of composite white carbon black: Boric acid (CAS No.: 10043-35-3) and terminal hydroxydimethoxysilane were dried in a vacuum drying oven at 120°C for 24 hours to remove moisture, 1.72 g of the dried terminal hydroxydimethoxysilane was poured into a high-temperature vacuum kneader, the reaction temperature was set to 180°C, and the temperature was gradually increased from room temperature at a rate of 10°C / min. When the temperature reached 140°C, 0.28 g of dried boric acid and 20 g of white carbon black (CAS No.: 10279-57-9) were added to the high-temperature vacuum kneader, stirring was started, the kettle was sealed, the temperature was continued to be increased to 180°C, and then the reaction was kept warm for 2 hours. After the reaction was completed, it was naturally cooled to obtain composite white carbon black.

[0029] Preparation of composite carbon nanotubes: Hexadecyltrimethylammonium bromide (CAS No.: 57-09-0) was mixed with 800 g of deionized water to prepare a hexadecyltrimethylammonium bromide aqueous solution with a hexadecyltrimethylammonium bromide concentration of 2 wt %. 6.06 g of modified carbon nanotubes were added to the hexadecyltrimethylammonium bromide aqueous solution and ultrasonically dispersed to obtain a carbon nanotube dispersion. 12.75 g of composite white carbon black was mixed with 200 g of deionized water and ultrasonically dispersed to obtain a white carbon black dispersion. The white carbon black dispersion was added to the hexadecyltrimethylammonium bromide aqueous solution and ultrasonically dispersed to obtain a white carbon black dispersion. The mixture was added into the carbon nanotube dispersion, and then filtered using a microporous filter membrane. The filtered powder was dried at 60°C for 6 hours to obtain a carbon nanotube-white carbon black composite. The polypropylene was dried in a vacuum drying oven at 90°C for 12 hours, the temperature of the mixing mill was set between 180 and 185°C, the roller speed was set at 15 to 20 r / min, 61.19 g of the dried polypropylene and the carbon nanotube-white carbon black composite prepared above were added, and the mixture was blended for 8 minutes to obtain a composite carbon nanotube.

[0030] Preparation of antistatic PE tube: 220 g of polyethylene, 45 g of composite carbon nanotubes, 30 g of EPDM rubber and 3 g of dispersant were mixed and added to an internal mixer for internal mixing. The components after internal mixing were transferred to a twin-screw extruder and extruded to obtain an antistatic PE tube.

[0031] Example 2 Preparation of modified carbon nanotubes: 300 g of deionized water, 0.72 g of polyvinyl pyrrolidone and 0.23 g of alkanolamine were mixed, and the mixture was stirred at a speed of 300 r / min for 15 min to obtain a mixed solution. 9.05 g of carbon nanotubes and 150 g of zirconia glass beads were added to the mixed solution, and the mixture was oscillated in an oscillating disperser at an ambient temperature of 25° C. for 6 h to obtain a carbon nanotube dispersion. The carbon nanotube dispersion prepared above was dried in a vacuum drying oven at 80° C. for 12 h to obtain modified carbon nanotubes.

[0032] Preparation of composite white carbon black: Boric acid and terminal hydroxydimethoxysilane were dried in a vacuum drying oven at 120°C for 24 hours to remove moisture, 1.69 g of the dried terminal hydroxydimethoxysilane was poured into a high-temperature vacuum kneader, the reaction temperature was set to 180°C, and the temperature was gradually increased from room temperature at a rate of 10°C / min. When the temperature reached 140°C, 0.31 g of dried boric acid and 20 g of white carbon black were added to the high-temperature vacuum kneader, stirring was started, the kettle was sealed, the temperature was continued to be increased to 180°C, and then the reaction was kept warm for 2 hours. After the reaction was completed, it was naturally cooled to obtain composite white carbon black.

[0033] Preparation of composite carbon nanotubes: The hexadecyltrimethylammonium bromide was mixed with 800g of deionized water to prepare a hexadecyltrimethylammonium bromide aqueous solution with a hexadecyltrimethylammonium bromide concentration of 2wt%, 5.84g of modified carbon nanotubes were added to the hexadecyltrimethylammonium bromide aqueous solution, and ultrasonic dispersion was performed to obtain a carbon nanotube dispersion; 15.77g of composite white carbon black was mixed with 200g of deionized water, and ultrasonic dispersion was performed to obtain a white carbon black dispersion, and the white carbon black dispersion was added to the carbon nanotube dispersion, and then filtered using a microporous filter membrane, and the filtered powder was dried at a temperature of 60°C for 6h to obtain a carbon nanotube-white carbon black composite; polypropylene was dried in a vacuum drying oven at 90°C for 12h, the temperature of the open mill was set between 180-185°C, the roller speed was 15-20r / min, 58.39g of the dried polypropylene and the carbon nanotube-white carbon black composite prepared above were added, and blended for 8min to obtain a composite carbon nanotube.

[0034] Preparation of antistatic PE tube: 260 g of polyethylene, 55 g of composite carbon nanotubes, 40 g of EPDM rubber and 5 g of dispersant were mixed and added to an internal mixer for internal mixing. The components after internal mixing were transferred to a twin-screw extruder and extruded to obtain an antistatic PE tube.

[0035] Example 3 Preparation of modified carbon nanotubes: 300 g of deionized water, 0.64 g of polyvinyl pyrrolidone and 0.23 g of alkanolamine were mixed, and the mixture was stirred at a speed of 300 r / min for 15 min to obtain a mixed solution. 9.13 g of carbon nanotubes and 150 g of zirconia glass beads were added to the mixed solution, and the mixture was oscillated in an oscillating disperser at an ambient temperature of 25° C. for 6 h to obtain a carbon nanotube dispersion. The carbon nanotube dispersion prepared above was dried in a vacuum drying oven at 80° C. for 12 h to obtain modified carbon nanotubes.

[0036] Preparation of composite white carbon black: Boric acid and terminal hydroxydimethoxysilane were dried in a vacuum drying oven at 120°C for 24 hours to remove moisture, 1.71 g of the dried terminal hydroxydimethoxysilane was poured into a high-temperature vacuum kneader, the reaction temperature was set to 180°C, and the temperature was gradually increased from room temperature at a rate of 10°C / min. When the temperature reached 140°C, 0.29 g of dried boric acid and 20 g of white carbon black were added to the high-temperature vacuum kneader, stirring was started, the kettle was sealed, the temperature was continued to be increased to 180°C, and then the reaction was kept warm for 2 hours. After the reaction was completed, it was naturally cooled to obtain composite white carbon black.

[0037] Preparation of composite carbon nanotubes: The hexadecyltrimethylammonium bromide was mixed with 800g of deionized water to prepare a hexadecyltrimethylammonium bromide aqueous solution with a hexadecyltrimethylammonium bromide concentration of 2wt%, 5.93g of modified carbon nanotubes were added to the hexadecyltrimethylammonium bromide aqueous solution, and ultrasonic dispersion was performed to obtain a carbon nanotube dispersion; 14.81g of composite white carbon black was mixed with 200g of deionized water, and ultrasonic dispersion was performed to obtain a white carbon black dispersion, and the white carbon black dispersion was added to the carbon nanotube dispersion, and then filtered using a microporous filter membrane, and the filtered powder was dried at a temperature of 60°C for 6h to obtain a carbon nanotube-white carbon black composite; polypropylene was dried in a vacuum drying oven at 90°C for 12h, the temperature of the open mill was set between 180-185°C, the roller speed was 15-20r / min, 59.26g of the dried polypropylene and the carbon nanotube-white carbon black composite prepared above were added, and blended for 8min to obtain a composite carbon nanotube.

[0038] Preparation of antistatic PE tube: 240 g of polyethylene, 40 g of composite carbon nanotubes, 35 g of EPDM rubber and 4 g of dispersant were mixed and added to an internal mixer for internal mixing. The components after internal mixing were transferred to a twin-screw extruder and extruded to obtain an antistatic PE tube.

[0039] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing the modified carbon nanotubes, 9.39 g of carbon nanotubes, 0.38 g of polyvinyl pyrrolidone, and 0.23 g of alkanolamine are used.

[0040] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing the modified carbon nanotubes, 8.89 g of carbon nanotubes, 0.89 g of polyvinyl pyrrolidone, and 0.22 g of alkanolamine are used.

[0041] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that when preparing the modified carbon nanotubes, an equal amount of alkanolamine replaces polyvinyl pyrrolidone.

[0042] Example 7 Example 7 is based on Example 6. The difference between Example 7 and Example 3 is that when preparing the modified carbon nanotubes, an equal amount of polyvinyl pyrrolidone is used to replace the alkanolamine.

[0043] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that when preparing the composite white carbon black, 1.77 g of terminal hydroxyl polydimethylsiloxane and 0.23 g of boric acid are used.

[0044] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that when preparing the composite white carbon black, 1.65 g of terminal hydroxyl polydimethylsiloxane and 0.35 g of boric acid are used.

[0045] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the composite carbon nanotubes, 6.3 g of modified carbon nanotubes, 10.71 g of composite white carbon black, and 62.99 g of polypropylene are used.

[0046] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that when preparing the composite carbon nanotubes, 5.63 g of modified carbon nanotubes, 18.03 g of composite white carbon black, and 56.34 g of polypropylene are used.

[0047] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, the modified carbon nanotubes are replaced with ordinary carbon nanotubes.

[0048] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, when preparing the carbon nanotube composite, an equal amount of the modified carbon nanotubes is replaced with composite white carbon black.

[0049] Comparative Example 2 Comparative Example 1 is based on Example 3. In Comparative Example 1, when preparing the carbon nanotube composite, an equal amount of composite white carbon black is replaced by modified carbon nanotubes.

[0050] The samples of Examples 1-12 and Comparative Examples 1-2 were sampled and the following performance tests were performed: (1) Antistatic performance test According to the GB / T 1410-2006 standard, the surface resistance of the sample is tested and the test results are filled in Table 1.

[0051] (2) Impact strength performance test Using ASTM D256 (1997) as the testing standard, the notched impact strength performance test of the samples was carried out, and the test results were filled in Table 1.

[0052] Table 1 Performance test results of Examples 1-12 and Comparative Example 1 Test specimen Resistivity / Ω·cm Notched impact strength / (J / m) Example 1 <![CDATA[5.5×10 4 ]]> 598 Example 2 <![CDATA[5.5×10 4 ]]> 587 Example 3 <![CDATA[5.3×10 4 ]]> 602 Example 4 <![CDATA[6.0×10 4 ]]> 575 Example 5 <![CDATA[5.8×10 4 ]]> 581 Example 6 <![CDATA[6.3×10 4 ]]> 564 Example 7 <![CDATA[6.2×10 4 ]]> 560 Example 8 <![CDATA[5.9×10 4 ]]> 574 Example 9 <![CDATA[5.9×10 4 ]]> 569 Example 10 <![CDATA[6.4×10 4 ]]> 554 Embodiment 11 <![CDATA[6.3×10 4 ]]> 559 Example 12 <![CDATA[7.2×10 4 ]]> 511 Comparative Example 1 <![CDATA[1.3×10 5 ]]> 481 Comparative Example 2 <![CDATA[1.7×10 5 ]]> 468 Combined with Table 1, it can be seen that the resistivity of Examples 1-3 is 5.5×104 or less, indicating that the PE pipe prepared in the present application has good antistatic properties, and the notched impact strength of Examples 1-3 is 587 J / m or more, indicating that the PE pipe prepared in the present application has good impact resistance.

[0053] The mass ratios of carbon nanotubes, polyvinyl pyrrolidone and alkanolamine in the modified carbon nanotubes of Examples 4 and 5 are not within the range defined in the present application. When the content of polyvinyl pyrrolidone is too little, it is difficult to further improve the dispersion of carbon nanotubes through its steric hindrance, and the electrostatic repulsion formed between alkanolamine and carbon nanotubes decreases. Therefore, the dispersibility of carbon nanotubes is difficult to improve, and carbon nanotubes agglomerate, affecting the stability of the system. Therefore, the antistatic performance and impact strength of Example 4 are both reduced; when the content of polyvinyl pyrrolidone is too much, it is difficult to further improve the dispersion improvement of carbon nanotubes, and too much polyvinyl pyrrolidone will also affect the overall stability of the system. Therefore, the impact strength of Example 5 decreases, and the antistatic performance is also affected.

[0054] In Example 6, no polyvinyl pyrrolidone was added when preparing the modified carbon nanotubes. In Example 7, no alkanolamine was added when preparing the modified carbon nanotubes. Only a single modification was performed on the carbon nanotubes, which made it difficult to synergistically enhance the dispersion effect on the carbon nanotubes. The stability of the carbon nanotubes with reduced dispersibility in the system decreased. Therefore, the antistatic properties and impact strength of Examples 6 and 7 were both reduced.

[0055] In Examples 8 and 9, when preparing composite silica, the terminal hydroxyl polydimethylsiloxane and boric acid used are not within the scope defined in the present application. When the boric acid content is too much or too little, the dynamic reversible performance of the BO electron bridge pair is affected, thereby affecting the damping performance of silica, and the viscosity of the system decreases. Therefore, the impact resistance of Examples 8 and 9 is reduced.

[0056] In Example 10 and Example 11, when preparing composite carbon nanotubes, the mass ratios of modified carbon nanotubes, composite silica and polypropylene are not within the range specified in the present application. When the content of composite silica is too little, silica is evenly distributed in the carbon nanotubes, but there are still parts of the carbon nanotubes that are not fully filled with silica, and the reinforcing effect on polypropylene is difficult to be further improved. At the same time, it is also difficult to improve the improvement performance of EPDM rubber, which affects the impact strength of the system. When the content of silica is too much, too much silica adheres to the surface of the carbon nanotubes, which affects the dispersion performance of the carbon nanotubes, and the carbon nanotubes agglomerate in the system, which affects the antistatic and impact resistance.

[0057] In Example 12, the modified carbon nanotubes are replaced with ordinary carbon nanotubes, and the unmodified carbon nanotubes agglomerate, which reduces the stability in the system, affects the antistatic properties and impact strength of the tubes, and the bonding performance between white carbon black and carbon nanotubes is difficult to be further improved. Therefore, the antistatic properties and impact strength of Example 12 are reduced.

[0058] In Comparative Example 1, the modified carbon nanotubes are replaced with composite silica. It is difficult for the system to form a more stable structure by only composite silica and polypropylene. The stability of the system is reduced, and the overall antistatic performance and mechanical strength are affected. Therefore, the antistatic performance and impact strength of Comparative Example 1 are reduced.

[0059] In Comparative Example 2, no composite white carbon is added to the composite carbon nanotubes. The stability of the composite carbon nanotubes prepared only by carbon nanotubes and polypropylene is difficult to improve, and the antistatic performance is reduced. At the same time, EPDM rubber cannot be combined with white carbon to improve performance, so the antistatic performance and impact strength of Comparative Example 1 are reduced.

[0060] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A composite carbon nanotube, characterized in that: The composite carbon nanotubes include modified carbon nanotubes, composite white carbon black and polypropylene; the modified carbon nanotubes include carbon nanotubes, polyvinyl pyrrolidone and alkanolamine.

2. The composite carbon nanotube according to claim 1, characterized in that: The modified carbon nanotubes are prepared by the following method: Water, polyvinyl pyrrolidone and alkanolamine are mixed and stirred to obtain a mixed solution, carbon nanotubes and zirconium oxide glass beads are added to the mixed solution, and the mixture is shaken in an oscillating disperser to obtain a carbon nanotube dispersion, and the carbon nanotube dispersion prepared above is dried to obtain modified carbon nanotubes.

3. The composite carbon nanotube according to claim 2, characterized in that: The mass ratio of the carbon nanotubes, polyvinyl pyrrolidone and alkanolamine is 1:(0.06-0.08):0.

025.

4. The composite carbon nanotube according to claim 1, characterized in that: The composite white carbon black is prepared by the following method: The terminal hydroxy dimethyl siloxane is heated, then mixed with boric acid and white carbon black, stirred and then kept warm for reaction, and then cooled after the reaction to obtain composite white carbon black.

5. The composite carbon nanotube according to claim 4, characterized in that: The mass ratio between the terminal hydroxyl polydimethylsiloxane and the boric acid is 1:(0.16-0.18).

6. The composite carbon nanotube according to claim 1, characterized in that: The composite carbon nanotubes are prepared by the following method: Hexadecyltrimethylammonium bromide, water and modified carbon nanotubes are mixed and dispersed to obtain a carbon nanotube dispersion; composite white carbon black and water are mixed and dispersed to obtain a white carbon black dispersion; the white carbon black dispersion is added to the carbon nanotube dispersion, filtered using a microporous filter membrane, and dried to obtain a carbon nanotube-white carbon black composite; polypropylene and the carbon nanotube-white carbon black composite are added to an open mill and blended to obtain composite carbon nanotubes.

7. The composite carbon nanotube according to claim 6, characterized in that: The mass ratio of the modified carbon nanotubes, composite white carbon black and polypropylene is 1:(2.2-2.7):

10. 8.An antistatic PE tube, characterized in that: The composition comprises the following components in parts by weight: 220-260 parts of polyethylene, 30-40 parts of ethylene propylene diene rubber, 3-5 parts of a dispersant, and 45-55 parts of the composite carbon nanotubes according to any one of claims 1-8.

9. A method for preparing the antistatic PE pipe according to claim 8, characterized in that: The steps include: The polyethylene, the composite carbon nanotubes, the EPDM rubber and the dispersant are mixed and added into an internal mixer for internal mixing. The components after internal mixing are transferred into a twin-screw extruder for extrusion molding to obtain an antistatic PE pipe.